Smart People Smart Ethics Seni Berorganisasi dalam Genggaman Gadget - Lili Nurlaili; Imas Masriah; Arkayah Pachelina; Fauziah Syafira Alfaini; Keken Thalia; Muhammad Hilmy Naufal; Poppy Octamelinia; Sahri Robi; Yanuarius Manggur (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
The digital age demands that Islamic boarding school students not only be proficient in religious studies but also skilled in managing organizations through information technology. This community service activity aims to equip students at the Al-Kaffah Islamic Boarding School with the concepts of “Smart People and Smart Ethics in running gadget-based organizations.” The primary issues identified were the still-predominantly consumptive use of gadgets and a lack of digital communication ethics in formal organizational coordination. The method employed was Participatory Action Research (PAR) through stages of digital ethics socialization, delivered via training sessions for the students. The expected outcome of this initiative is to enhance the students’ awareness of positioning gadgets as tools to support da’wah and organizational activities, rather than merely as entertainment devices. The students began adopting the “Smart People” principle, meaning they should not only be skilled in using gadgets but must also be wise users—such as using polite language when coordinating in digital chat groups. This activity concludes that empowering students through civilized digital literacy is key to shaping future leaders who are ready to face the challenges of the times without losing their identity as students in the future.